Match-up on Physical Attractiveness: Effectiveness of Cartoon Spokes-Character and Human Spokesperson - Mishra, Aditya S. (Indian Journal of Marketing, 2014)
Marketers have been selecting celebrities to endorse their brands on the basis of their physical attractiveness. Consumers tend to form positive stereotypes about such people because they assume that the endorsers, who are ranked high on one dimension, would excel on other dimensions as well. However, attractive endorsers were found enhancing consumers' favourable attitudes in case of 'matching/congruent' attractiveness related products only. Therefore, the first objective of this conceptual paper is to frame propositions to demonstrate the congruence effect in case of spokes-characters too. Hence, in first part of the study, the propositions related to the impact of attractive/unattractive spokes-characters in terms of product types (attractiveness related vs. attractiveness un-related) have been framed. The second part of the paper is based on the 'distinctiveness' theory which says that an ad having certain stimuli different from similar ads would catch more attention of the target audience and would have a more favourable impact on consumer attitudes. Therefore, the second objective of the paper is to compare the ad- and product-based attitude of attractive human spokesperson and attractive cartoon spokes-characters in terms of product types. All the three propositions presented in the present paper can be empirically tested by researchers in the future.